Deutsch im Sprachvergleich. Grammatische Kontraste und Konvergenzen - Gunkel, Lutz (Jahrbuch des Instituts für Deutsche Sprache, 2012)
Cross-language comparison can show where German structures diverge from and converge with those of other languages. The essays in the 2011 Yearbook of the Institute for German Language compare German with other languages on all grammatical levels, from photetics, phonology, graphematics, and morphology to syntax, semantics, pragmatics, and text grammar. In addition, the book presents new methods of language comparison from corpus linguistics. The volume is intended for linguists of German or related languages as well as for teachers of German as a second language.